SISTEM INFORMASI BANK DATA KECAMATAN SUKAJADI UNTUK MEWUJUDKAN PEKANBARU SEBAGAI SMART CITY MADANI - Andin Niantima Prima Sari (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2022)
The lack of data availability is a separate problem in Sukajadi District. This resulted in every request for any data, especially social conditions, be it economy, health, education at the sub-district or RT and RW levels, data collection was always repeated many times. Therefore it is necessary to develop an information system to overcome this problem. The information system is called the District Data Bank. The method used in this study is a descriptive qualitative method with research on the preparation of data bank applications. This database information system is important because the sub-district is the OPD closest to the community so that the sub-district can provide one data at hand that can be used for strategic decision-making by the related technical OPD. Keywords: sustainable development, data bank, realtime and accurate data